CD4/CD8 Ratio and Cancer Risk Among Adults With HIV. (16th March 2022) - Castilho, Jessica L; Bian, Aihua; Jenkins, Cathy A; Shepherd, Bryan E; Sigel, Keith; Gill, M John; Kitahata, Mari M; Silverberg, Michael J; Mayor, Angel M; Coburn, Sally B; Wiley, Dorothy; Achenbach, Chad J; et al.
Abstract: Background: Independent of CD4 cell count, a low CD4/CD8 ratio in people with HIV (PWH) is associated with deleterious immune senescence, activation, and inflammation, which may contribute to carcinogenesis and excess cancer risk. We examined whether low CD4/CD8 ratios predicted cancer among PWH in the United States and Canada. Methods: We examined all cancer-free PWH with 1 or more CD4/CD8 values from North American AIDS Cohort Collaboration on Research and Design observational cohorts with validated cancer diagnoses between 1998 and 2016. We evaluated the association between time-lagged CD4/CD8 ratio and risk of specific cancers in multivariable, time-updated Cox proportional hazard models using restricted cubic spines. Models were adjusted for age, sex, race and ethnicity, hepatitis C virus, and time-updated CD4 cell count, HIV RNA, and history of AIDS-defining illness. Results: Among 83 893 PWH, there were 5628 incident cancers, including lung cancer (n = 755), Kaposi sarcoma (n = 501), non-Hodgkin lymphoma (n = 497), and anal cancer (n = 439). The median age at cohort entry was 43 years. The overall median 6-month lagged CD4/CD8 ratio was 0.52 (interquartile range = 0.30-0.82). Compared with a 6-month lagged CD4/CD8 of 0.80, a CD4/CD8 of 0.30 was associated with increased risk of any incident cancer (adjusted hazard ratio = 1.24 [95% confidence interval = 1.14 to 1.35]). The CD4/CD8 ratio was also inversely associated with non-Hodgkin lymphoma, Kaposi sarcoma, lung cancer, anal cancer, and colorectal cancer in adjusted analyses (all 2-sided P < .05). Results were similar using 12-, 18-, and 24-month lagged CD4/CD8 values. Conclusions: A low CD4/CD8 ratio up to 24 months before cancer diagnosis was independently associated with increased cancer risk in PWH and may serve as a clinical biomarker.